Accurate activity determination of a californium neutron source. (April 2023) - Stonaha, P.J.; Harper, C.; Tan, C.; Urban-Klaehn, J.; Taylor, C.N.; Forest, T.; Dale, D.
Abstract: Accurately counting analog events requires constructing an electronics chain that produces one count for each input pulse. In this work we review the use of Nuclear Instrumentation Module electronic units for counting neutron capture events in a 3 He tube. We identify two unique types of false trigger events in a leading-edge discriminator and show how a dual timer module can be used to produce a veto window to exclude these events. We use the constructed electronics chain to build an apparatus to measure neutron pulses from a 252 Cf neutron source. We compare the measurements with a Monte Carlo N-Particle (MCNP) model to determine the activity of the neutron source. Furthermore, by making additional measurements with borated polyethylene attenuators between the source and detector, we are able to determine the boron concentration of the polyethylene. This technique provides accurate determination of the source activity to a precision of 2.8% at the k = 1 level. The method used is simple, inexpensive, and requires no additional calibrated instruments. Highlights: 252 Cf activity is accurately determined using a small neutron-shielding apparatus Determination of source activity is comparable to NIST-standardized methods CAEN Leading Edge Discriminators exhibit consistent false positives A Dual Timer module is used to accurately veto false positives